Biology, taxonomy, genetics, and management of Zymoseptoria tritici: the causal agent of wheat leaf blotch - Girma Ababa (Mycology, 2023)
ABSTRACTSeptoria tritici blotch or Septoria leaf blotch has been used for long time, but leaf blotch is a correct disease name. Moreover, Lb resistant gene is the correct name, but, not Stb gene. It has sexual and asexual parts on the mycelia, known as heterothallic fungi. Its pathogenic diversity ranged from 40% to 93% and has produced a wide variety of AvrLb6 haplotypes. M. graminicola has a plasmogamy and karyogamy sexual process. The pathogen can use macropycnidiospores, micropycnidiospores, and pycnidia vegetative growths for infection and overwintering. Synthetic M3, Kavkaz-K4500, Synthetic 6×, and TE9111 wheat genotypes have horizontal resistance. Avirulence (Avr) genes in Z. tritici and their matching wheat (R) genes indicate gene for gene mechanisms of resistance. Twenty-two R genes (vertical resistance) have been identified. In both horizontal and vertical resistance, different Lb genes have been broken down due to new Z.tritici virulent gene and currently Lb19 resistant gene is being recommended. Mixing of resistant and susceptible cultivars is also the most effective management strategy. Moreover, different cultural practices and biological control have been proposed. Lastly, different fungicides are also available. However, in developing countries cultivar mixture, isolates diversity, biological control, and epidemic studies have been greatly missed.